Sustainable membrane technology for resource recovery from wastewater: Forward osmosis and pressure retarded osmosis. (February 2021) - Chia, Wen Yi; Chia, Shir Reen; Khoo, Kuan Shiong; Chew, Kit Wayne; Show, Pau Loke
Graphical abstract: Highlights: FO and PRO are promising in treating wastewaters and recovering useful resources. Eliminating DS recovery process and exploring new industrial area are important. PRO can be economical feasible and cost competitive with other renewable energies. The minimum power density to make PRO economical is much higher than 5 W/m 2 . Hybrid and dual system of PRO could provide more benefits over the standalone PRO. Abstract: There has been increasing attention in osmotically driven membrane processes (ODMPs), which include forward osmosis (FO) and pressure retarded osmosis (PRO). They provide a sustainable solution against water and energy scarcity issues by utilizing the osmotic pressure difference between two water bodies, feed (low salinity) and draw solution (high salinity), across a semipermeable membrane. Indeed, their main applications, water treatment (e.g., desalination and wastewater treatment) and power generation, facilitate resource recovery from wastewaters. This review updates the recent development of FO and PRO by providing a comprehensive review on their fundamentals, membrane properties, potential applications as well as advanced techniques. In addition, economic analysis and environmental impacts are critically reviewed to highlight their feasibility and sustainability. Resource recovery from wastewaters (e.g., water, nutrient and energy) using FO and PRO is also discussed followed by their commercialization and future trends in order to push forward laboratory research to full-scale commercialization.